2018
DOI: 10.1002/jcp.26313
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf homolog 3 (DKK3): A candidate for detection and treatment of cancers?

Abstract: Wnt signaling is an evolutionary highly conserved pathway that is modulated by several inhibitors and activators, and plays a key role in numerous physiological processes. One of the extracellular Wnt inhibitors is the DKK (Dickkopf Homolog) family which has four members (Dkk1-4) and a unique Dkk3-related gene, Dkkl1 (soggy). DKK3 is a divergent member of the DKK protein family. Evidence suggests that DKK3 may serve as a potential therapeutic target in several types of human cancers. We review here the biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…In our study, LINC00261 is expressed at a low level in prostate cancer, and LINC00261 negatively correlates with prostate cancer progression. Increasing studies have demonstrated that the aberrant expression of DKK3 is associated with the proliferation and tumor development and it is already considered to be a biomarker and therapeutic target in many cancers [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, LINC00261 is expressed at a low level in prostate cancer, and LINC00261 negatively correlates with prostate cancer progression. Increasing studies have demonstrated that the aberrant expression of DKK3 is associated with the proliferation and tumor development and it is already considered to be a biomarker and therapeutic target in many cancers [7].…”
Section: Discussionmentioning
confidence: 99%
“…As a divergent member of the Dickkopf (DKK) family, the Dickkopf-related protein 3 (DKK3) is a tumor suppressor involved in slowing down the progressions of many types of cancer. For example, DKK3 is expressed at a low level in endometrial cancer, indicating that DKK3 can also be used as a new biomarker in endometrial cancer [7]. In addition, a recent study has shown that induction of DKK3 can inhibit prostate cancer development [8].…”
Section: Introductionmentioning
confidence: 99%
“…DKK3, found to be increased at the gene and protein level in FCA, is considered to be a tumor suppressor involved in several cancers [ 57 ] and, most interestingly, described as required for maintaining the integrity of secretory vesicles in mouse adrenal glands [ 58 ]. Further studies with regard to this marker might reveal its role in modulating both hormone production and tumor growth restriction in corticotroph adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, DKK3 was shown to attenuate CD133-induced NK-cell activation by inhibiting the Erk pathway and immunological synapse formation (27). DKK3 was also found to act as a biomarker and a therapeutic target by modulating Wnt signaling in several types of human cancer (28). However, the role of DKK3 in TC remains understudied.…”
Section: Discussionmentioning
confidence: 99%